Romania: Positive Law and Top‑Down Social Engineering of Families Through Legal Means - Floare, Marius; Florian, Emese (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
Like most of Central Europe, Romania has observed a steady demographic decline since the 1990s due to extensive emigration and a decrease in the total fertility rate. Attempts have been made, particularly since 2010, to reverse this decline and increase the total birth rate. A very generous child-rearing leave and corresponding child-rearing allowance contributed to a slight increase in the number of live births per woman, which became one of the highest in the European Union (EU) in the late 2010s. Although the improved economic outlook since joining the EU was also a factor, this chapter aims to identify all the domestic legal norms that promote family growth. The chapter looks at the broad picture of governmental family policy in Romania, taking into account the differences between its relatively conservative family law and its more progressive social law, the latter of which offers a wide array of benefits and maintains a broad definition of families. Non-traditional methods of increasing childbirths, such as surrogacy and fertility treatments, are also considered, and the normative deficiencies in this regard are exposed. The chapter focuses on the positive law, with very brief incursions into prior legal norms insofar as they are relevant to show the durable trends in public policy. Keywords: family, spouse, children, allowance, accommodation, fertility